Related biomarkers of neurocognitive impairment in children with obstructive sleep apnea. (January 2019) - Shi, Yewen; Luo, Huanan; Liu, Haiqin; Hou, Jin; Feng, Yani; Chen, Jinwei; Xing, Liang; Ren, Xiaoyong
Abstract: Objectives: Different experiment approaches have demonstrated that children with obstructive sleep apnea (OSA) exhibit neurocognitive and behavioral deficits. This review summarized the potential biomarkers of OSA-associated neurocognitive impairment in children. Methods: A scoping review of studies on children with OSA that evaluated the potential value of different markers in identifying neurocognitive impairment was undertaken. Additionally, the biomarkers were categorized according to the different research methods, including brain imaging studies, serological indicators and urine markers. Results: Majority of the studies that evaluated blood biomarkers, plasma insulin growth factor-1 (IGF-1) and Alzheimer's disease (AD)-related biomarkers appeared to exhibit a favorable profile, and could discriminate between OSA children with or without neurocognitive impairments. Brain imaging studies and urinary neurotransmitters could also be helpful for screening OSA cognitive morbidity in children. Conclusion: Due to limited research methods available in children, the cognitive susceptibility of children with OSA has been rarely studied. The main reason for this may be the limited research methods in children. Numerous study populations of children and complex psychological tests are required, which involve major labor and costs.Multi-center prospective studies are needed to identify suitable biomarkers for the timely prediction and effective intervention to prevent neurocognitive impairment in children with OSA and to explore further opportunities in this arena.